2023
DOI: 10.1007/s12664-022-01333-5
|View full text |Cite
|
Sign up to set email alerts
|

Indian consensus statements on irritable bowel syndrome in adults: A guideline by the Indian Neurogastroenterology and Motility Association and jointly supported by the Indian Society of Gastroenterology

Abstract: The Indian Neurogastroenterology and Motility Association (INMA), earlier named the Indian Motility and Functional Diseases Association developed this evidence-based practice guidelines for the management of irritable bowel syndrome (IBS). A modified Delphi process was used to develop this consensus containing 28 statements, which were concerning diagnostic criteria, epidemiology, etiopathogenesis and comorbidities, investigations, lifestyle modifications and treatments. Owing to the Coronavirus disease-19 (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 136 publications
1
7
0
Order By: Relevance
“…2 This could be attributed to a higher fiber intake in the Indian population compared with the western world. There were studies that showed high prevalence of constipation in pregnancy and puerperium, ranging from 45% to 55% like those by Goshal et al 3 and Beksac et al 4 This can be attributed to the lower fiber consumption in western countries. On the other hand, lower prevalence, ranging between 4.5% and 13%, were shown in a few studies, such as those by Shi et al 5 and Van Brummen et al.…”
Section: Discussionmentioning
confidence: 93%
“…2 This could be attributed to a higher fiber intake in the Indian population compared with the western world. There were studies that showed high prevalence of constipation in pregnancy and puerperium, ranging from 45% to 55% like those by Goshal et al 3 and Beksac et al 4 This can be attributed to the lower fiber consumption in western countries. On the other hand, lower prevalence, ranging between 4.5% and 13%, were shown in a few studies, such as those by Shi et al 5 and Van Brummen et al.…”
Section: Discussionmentioning
confidence: 93%
“…Making abdominal pain mandatory in the Rome IV criteria and raising its frequency threshold 7 would be expected to have major impact on the diagnostic performance of the Rome IV criteria in these population as the frequency and severity of abdominal pain have been shown to be less in these parts of the World. 9,10 Application of the Rome IV criteria in subjects meeting the III IBS criteria resulted in an internal shift in the diagnostic categories to other subtypes of DGBI (Figure 4). This is not unexpected as the Rome IV criteria require abdominal pain and its frequency threshold was changed to at least 1 day per week from at least 3 days a month.…”
Section: Discussionmentioning
confidence: 99%
“…There is no study to date on the diagnostic performance of the Rome IV criteria as compared to the Rome III criteria in an Indian and Bangladeshi population. Making abdominal pain mandatory in the Rome IV criteria and raising its frequency threshold 7 would be expected to have major impact on the diagnostic performance of the Rome IV criteria in these population as the frequency and severity of abdominal pain have been shown to be less in these parts of the World 9,10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations